Traditional Detection of Intestinal Helminths in Stray Cats in Wasit Province, Iraq - Aqeele, Ghasik (Journal La Lifesci, 2024)
The purpose of this study was to find out the prevalence and distribution of intestinal parasites namely helminths in stray cats in different areas of Wasit Province, Iraq with reference to zoonotic risks for improved public health intervention. The study included a survey of helminthes in the intestines of stray cats in several areas of Wasit province, to determine the extent of their spread among populations in the regions. Samples were collected from 96 stray cats distributed from several areas of the same province, 7 species of parasitic were observed, in the intestines and four species tapeworms. The highest observed was of Dipylidium caninum for 44.61% of cats stray infected with tapeworms. The other two species recorded nematodes as 46.51%, and 22.58% for Toxocara cains, and Toxascaris leonina respectively, note that T. cains infection is higher than the others; while, other species have been diagnosed with different rates 35.38%, 24.61%, 12.30%, and 27.90% for Taenia multiceps, Taenia ovis, Taenia pisiformis, and Ancylostoma sp., respectively. The infection rate in the northern regions of the province was higher in cats than in the southern regions of Wasit Province with nematodes and tapeworms. The extensive presence of stray cats across numerous Iraqi areas necessitates increased focus from relevant bodies, especially in public health and veterinary sectors, to mitigate associated risks and zoonotic concerns. Consequently, necessary to enhance the scope of studies and investigations concerning cats and their ailments, attributed to the proliferation of feline reproduction within communities and their interaction with stray felines.